let C be complete Lattice; :: thesis: for X being set holds "\/" (X,C) = "/\" ( { a where a is Element of C : a is_greater_than X } ,C)
let X be set ; :: thesis: "\/" (X,C) = "/\" ( { a where a is Element of C : a is_greater_than X } ,C)
set Y = { a where a is Element of C : a is_greater_than X } ;
A1: "\/" (X,C) is_less_than { a where a is Element of C : a is_greater_than X }
proof
let a be Element of C; :: according to LATTICE3:def 16 :: thesis: ( a in { a where a is Element of C : a is_greater_than X } implies "\/" (X,C) [= a )
assume a in { a where a is Element of C : a is_greater_than X } ; :: thesis: "\/" (X,C) [= a
then ex b being Element of C st
( a = b & b is_greater_than X ) ;
hence "\/" (X,C) [= a by Def21; :: thesis: verum
end;
X is_less_than "\/" (X,C) by Def21;
then "\/" (X,C) in { a where a is Element of C : a is_greater_than X } ;
then for b being Element of C st b is_less_than { a where a is Element of C : a is_greater_than X } holds
b [= "\/" (X,C) ;
hence "\/" (X,C) = "/\" ( { a where a is Element of C : a is_greater_than X } ,C) by ; :: thesis: verum